Effect of human amniotic epithelial cells on pro‐fibrogenic resident hepatic cells in a rat model of liver fibrosis. Issue 2 (3rd November 2017) - Cargnoni, Anna; Farigu, Serafina; Cotti Piccinelli, Ester; Bonassi Signoroni, Patrizia; Romele, Pietro; Vanosi, Graziella; Toschi, Ivan; Cesari, Valentina; Barros Sant'Anna, Luciana; Magatti, Marta; Silini, Antonietta R.; Parolini, Ornella
Abstract: Myofibroblasts are key fibrogenic cells responsible for excessive extracellular matrix synthesis characterizing the fibrotic lesion. In liver fibrosis, myofibroblasts derive either from activation of hepatic stellate cells (HSC) and portal fibroblasts (PF), or from the activation of fibroblasts that originate from ductular epithelial cells undergoing epithelial–mesenchymal transition. Ductular cells can also indirectly promote myofibroblast generation by activating TGF‐β, the main fibrogenic growth factor, through αvβ6 integrin. In addition, after liver injury, liver sinusoidal cells can lose their ability to maintain HSC quiescence, thus favouring HSC differentiation towards myofibroblasts. The amniotic membrane and epithelial cells (hAEC) derived thereof have been shown to decrease hepatic myofibroblast levels in rodents with liver fibrosis. In this study, in a rat model of liver fibrosis, we investigated the effects of hAEC on resident hepatic cells contributing to myofibroblast generation. Our data show that hAEC reduce myofibroblast numbers with a consequent reduction in fibronectin and collagen deposition. Interestingly, we show that hAEC strongly act on specific myofibroblast precursors. Specifically, hAEC reduce the activation of PF rather than HSC. In addition, hAEC target reactive ductular cells by inhibiting their proliferation and αvβ6 integrin expression, with a consequent decrease in TGF‐β activation. Moreover, hAEC counteract the transition of ductular cells towards fibroblasts, while it does not affect injury‐induced and fibrosis‐promoting sinusoidal alterations. In conclusion, among the emerging therapeutic applications of hAEC in liver diseases, their specific action on PF and ductular cells strongly suggests their application in liver injuries involving the expansion and activation of the portal compartment.